Benign intermuscular lipoma in a bitch - Thilagar, S.; Toe, I; Hii, K. L.; Abdul Rahman, Sheikh Omar; Ching, T. S. (Veterinary Association Malaysia, 2005)
A case of intermuscular lipoma located between the external abdominal oblique and internal abdominal oblique muscles in a fourteen- year -old dog is described. Presenting signs, radiographic findings, surgical treatments and the follow-up treatment are discussed.